Menerapkan Prinsip Nilai dan Moral Islam dalam Perpindahan Hak Kepemilkan dada E-Commerce dengan Sistem Cash On Delivery - Widiastuti, Dwi Suci; Jubaedah, Dedah (BISMA : Business and Management Journal, 2024)
The development of e-commerce has changed how transactions are carried out, including the transfer of ownership rights of goods. One popular payment method in e-commerce transactions is Cash on Delivery (COD), which allows consumers to pay for goods upon receipt. From the Islamic values and morals perspective, ensuring that this transaction system runs by sharia principles is essential. This study aims to analyse the application of Islamic tenets in transferring ownership rights through the COD system in e-commerce. The main principles of concern are justice, honesty, and transparency, which are reflected in the prohibition of the practice of usury, gharar (uncertainty), and maysir (speculation). This study uses a qualitative approach with literature analysis related to Islamic law and the concept of transfer of ownership rights in muamalah fiqh. The results of the study show that the COD system in e-commerce can be accepted within the sharia framework if it meets several requirements, such as a clear agreement between sellers and buyers, as well as clarity in the description of goods and prices. Additionally, it is important to avoid fraud and ensure the rights of both parties are protected, in accordance with the principles of fair transactions in Islam.